2020
DOI: 10.1186/s13007-020-00571-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic material basis of traditional Chinese medicine based on biomacromolecules: a review

Abstract: Biomacromolecules, the first components of bioactive substances in traditional Chinese medicines (TCM) have wide bioactivity-related efficacy but have not yet been fully appreciated compared to small molecule components. The present review brings a novel and systemic point of view to deepen the understanding of the pharmacodynamic material basis of TCM based on biomacromolecules (polysaccharides, proteins and nucleic acids). Biomacromolecules have been, are and will have considerable roles in the efficacy of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 111 publications
0
26
0
Order By: Relevance
“…If the spleen is healthy, the other four viscera are healthy, and the melancholia resolves itself. The Chinese traditional incense consisting mainly of AR, Phellodendri Chinensis Cortex, and Artemisiae Argyi Folium has demonstrated the advantages of Chinese medicine in “avoid poisonous gas” in the prevention of the novel coronavirus COVID-19 ( Zhang et al, 2020 ). “AR could warm the stomach, transport food and increase appetite” when combined with Galli Gigerii Endothelium Corneum, and it can promote appetite and increase the effect of Galli Gigerii Endothelium Corneum on relieving food and guiding stagnation ( Tao, 2013 ).…”
Section: Traditional Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…If the spleen is healthy, the other four viscera are healthy, and the melancholia resolves itself. The Chinese traditional incense consisting mainly of AR, Phellodendri Chinensis Cortex, and Artemisiae Argyi Folium has demonstrated the advantages of Chinese medicine in “avoid poisonous gas” in the prevention of the novel coronavirus COVID-19 ( Zhang et al, 2020 ). “AR could warm the stomach, transport food and increase appetite” when combined with Galli Gigerii Endothelium Corneum, and it can promote appetite and increase the effect of Galli Gigerii Endothelium Corneum on relieving food and guiding stagnation ( Tao, 2013 ).…”
Section: Traditional Usesmentioning
confidence: 99%
“…A putative sesquiterpenoid biosynthetic pathway was proposed, including mevalonate, 2-C-methyl-d-erythritol-4-phosphate, sesquiterpene synthase, cytochrome P450, and the peroxisome pathway ( Chen et al, 2017 ). However, increasing studies showed that macromolecular substances (e.g., polysaccharides and proteins) play an indispensable role in the quality formation of TCM ( Zhang et al, 2020 ). The biomacromolecules in AR have wide bioactivity-related efficacy but yet to be fully appreciated compared with small molecule components.…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive small peptides are composed of 2–10 amino acids linked by peptide bonds. Studies have found that amino acids such as Trp, Tyr, Met, Gly, Cys, His, and Pro in the peptide chain can significantly improve the bioactivity [ 23 , 24 ]. In other words, compared with traditional chemotherapy drugs, small peptides have several advantages, such as high absorption, small size, well-defined signaling targets, and minimal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Each materia medica contained many formulae, with each formula comprising a combination of herbal drugs. Among these, complex components including carbohydrates/polysaccharides (PS), proteins/peptides, glycolipids/ glycoproteins, lipids, together with their metabolic derivatives such as glycosides, amines, fatty acids, flavonoids, terpenoids, phenols, and alkaloids intimately interacted with each other and modulated biological responses of immune cells and the hosts (Li and Kan, 2017;Yu et al, 2018b;Zhang et al, 2020c). Differential agonistic, compatible, or antagonistic interactions occur among TCM herbal ingredients.…”
Section: Introductionmentioning
confidence: 99%